PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Satyawan, I Putu Adi; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
The purpose of this study was to determine the effect of transformational leadership, Job Satisfaction, and Organizational Commitment on Organizational Citizenship Behavior at UD. Kariasih in Mengwi Badung. The population used in this study were all employees UD. Kariasih totaling 46 respondents to the study, thus this study using saturated sample. Data collected through interviews and questionnaires. The analysis technique used is multiple linear regression analysis. The theory in this study using social exchange theory. Based on the results of the analysis show transformational leadership, job satisfaction and organizational commitment and significant positive effect on organizational citizenship behavior. This shows that the better the transformational leadership, job satisfaction and organizational commitment will increase organizational citizenship behavior of employees. The company UD. Kariasih in Mengwi Badung must always consider the level of transformational leadership, job satisfaction and organizational commitment that is felt by employees.
Keywords: transformational leadership, job satisfaction, organizational commitment, organizational citizenship behavior